ATOMS: ALMA Three-millimeter Observations of Massive Star-forming regions–VI. On the formation of the 'L' type filament in G286.21+0.17. Issue 3 (2nd October 2021) - Zhou, Jian-Wen; Liu, Tie; Li, Jin-Zeng; Liu, Hong-Li; Wang, Ke; Xu, Feng-Wei; Kim, Kee-Tae; Lee, Chang Won; Dewangan, Lokesh; Tatematsu, Ken'ichi; Li, Shanghuo; Liu, Xun-Chuan; et al.
ABSTRACT: Filaments play an important role in star formation, but the formation process of filaments themselves is still unclear. The high-mass star-forming clump G286.21+0.17 (G286 for short) that contains an 'L' type filament was thought to undergo global collapse. Our high-resolution ALMA band 3 observations resolve the gas kinematics of G286 and reveal two sub-clumps with very different velocities inside it. We find that the 'blue profile' (an indicator of gas infall) of HCO + lines in single dish observations of G286 is actually caused by gas emission from the two sub-clumps rather than gas infall. We advise great caution in interpreting gas kinematics (e.g. infall) from line profiles towards distant massive clumps in single dish observations. Energetic outflows are identified in G286 but the outflows are not strong enough to drive expansion of the two sub-clumps. The two parts of the 'L' type filament ('NW–SE' and 'NE–SW' filaments) show prominent velocity gradients perpendicular to their major axes, indicating that they are likely formed due to large-scale compression flows. We argue that the large-scale compression flows could be induced by the expansion of nearby giant H ii regions. The 'NW–SE' and 'NE–SW' filaments seem to be in collision, and a large amount of gas has been accumulated in the junction region where the most massive core G286c1 forms.